The Phenomenon of Adolescent Behavior in Consuming Liquor in Sidorejo Village, Saradan District, Madiun Regency - Eka Lestari Widyaningrum; Suhadi Prayitno; Riska Ratnawati (International Journal Labs, 2024)
Adolescence is one of the periods of human development, this period is a period of change or transition from childhood to adulthood which includes biological, psychological and social changes. Deviant behavior and crimes committed by adolescents are also increasingly diverse, one of which is consuming alcohol. The research method used in this research is a qualitative method with a phenomenological approach that aims to determine the exploitation behavior of ladies companion. The informants in this study were 8 teenagers in Sidorejo Village, Saradan District, Madiun Regency. Conduct validity and reliability by triangulating sources and techniques. Source triangulation was conducted on teenagers, parents, and alcohol sellers. While the technique with Voice Recording and Documentation. The results of research conducted on 8 informants obtained a statement that all informants consume liquor. Some of the factors of teenagers consuming liquor are from the factors of Knowledge, Attitude, Access to places to buy and sell liquor, the Role of Parents, and the influence of peers. The conclusion of this study is that all informants feel that consuming alcohol is likely to be formed because of the culture of alcohol consumption in Sidorejo Village, Saradan District. Suggestions for adolescents by providing knowledge so that it is not easy to fall into Liquor Consuming Behavior.